Sociolinguística cognitiva: um outro olhar para a variação linguística. - Marcilene da Silva Cavalcante (Nepan editor, 2021)
The main objective of this paper is to show the intersection between variationist sociolinguistics and cognitive linguistics, which resulted in a new side of linguistics: cognitive sociolinguistics. In this mea-ning, a theoretical exposition was made on the referred areas, their main concepts and contributions, based on the studies by Silva (1997) and Ferrari (2016). In data analysis, oral samples were collected from 18 resi-dents of the City of Tabatinga in Amazonas. The results proved that there is a semantic variation in the use of ‘mesmo’ and, at the same time, in the contexts there is of conceptual perspective operation as Langacker’s prominence (2008).